(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Neck circumference (NC) is a relatively new anthropometric measure of differentiating body fat distribution and considered as a marker of upper subcutaneous adiposity. Aims and Objectives: The present study was undertaken to assess the suitability and cut-offs estimation of NC to determine overweight and obesity in Asian Indian adults. Materials and Methods: The present cross-sectional study was carried out among 1830 adults (914 males; 916 females) aged 20-49 years of Karbi-Anglong, Northeast-India, using multistage-stratified sampling method. Height, weight, waist circumference (WC) and neck circumference (NC) were recorded using standard procedures. The body mass index (BMI kg m−2) was calculated and overweight and obesity were assessed using standard cut-offs. Results: Linear and binary logistic regression analyses showed that NC had a better predictive value of BMI (p<0.001). The ROC-AUC results showed that NC seems to have relatively better predictive value in greater adiposity (BMI≥30.00 kg m−2) among both males (AUC 0.83, 95% CI: 0.81-0.86) and females (AUC 0.88, 95%CI: 0.85-0.89) (p<0.01). The cut-offs of NC were observed to be 36.0 cm and 38.0 cm (in males) and 30.9 cm and 33.0 cm (in females) for BMI ≥25.00 kg m−2 and BMI 30 kg m−2, respectively. Conclusion: Further studies should be undertaken to determine and validate the existing and/or newly proposed cut-offs among larger samples for pan-Indian cut-offs for the assessment of overweight and obesity and related risks of non-communicable diseases and metabolic disorders.